Emerging trends and innovations in privacy and health information management - Albuquerque, Cristina Maria Pinto (IGI Global, 2019)
"This book examines the social, ethical, and scientific issues surrounding the use of technology in the management of health services and in the provision of care in medical facilities"--Provided by publisher